The efficiency of different combinations of lactate and fresh adapted mixtures in infants of the first half-year of life on artificial feeding - T. N. Elkina; E. A. Surovikina (Лечащий Врач)
Infant formula with probiotics has an important influence on the formation of the intestinal microbiocenosis in children deprived of breast milk. Special attention should be given to baby milk formula. which in the process of milk fermentation, gets unique properties which allows to prescribe them with therapeutic and preventive purposes, including for relief of functional disorders of the digestive system.